Um ser de lá do sertão e a construção da(s) suas(s) identidade(s) no discurso cancionista nordestino - Costa, José Zilmar Alves da (2005)
This work was formulated in order to study the use of words in a specific sphere of human communication - the world of music. From a selection of compositions by Luiz Gonzaga (1912 -1989) and partners, the research goes in search of the identity(ies) of the migrant from Brazilian Northeast's "sertão". The work uses a discursive analysis based on a theoretical framework strongly supported by Mikhail Bakhtin's reflections and whose thread is the theme of migration discussed by Zygmunt Bauman. Thus, this qualitative and interpretivist research focuses on a particular type of text, originating from a specific sphere of human communication that is roughly known as "lyrics" ("words of songs")